PERUBAHAN GARIS PANTAI DESA BENTENAN KECAMATAN PUSOMAEN, MINAHASA TENGGARA - Opa, Esry T (Sam Ratulangi University, 2011)
ABSTRACTBentenan village, located on the East coast of Minahasa peninsula and surrounded by gently sloping hills, has a shoreline of 1.3 km. The shape of the shoreline is curved facing Bentenan Island. It is observed that coastline had been gradually retreating. Research and data collection on the coastline has been conducted in November 2008. As many as 85 points have been plotted using GPS, rectified with LPI maps and compared with a couple of old maps, i.e., Peta Dishidros Lembar 334 1992 and Peta Laut No. 62 1985. Shoreline of Bentenan village shown to be retreated 165 meters in average towards the mainland from 1985 to 2008 (23 years), averaging a decrease of 7.17 meters. This indicates that the shore of Bentenan undergoes a process of erosion/ abrasion which causes changes in shoreline backwards towards the land, also called beach retreat.Keywords: Bentenan, shorelines, Abrasion, beach retreat, geomorphology.ABSTRAKDesa Bentenan memiliki panjang garis pantai sekitar 1,3 km, terletak di pantai Timur semenanjung Minahasa yang bertopografi landai dan dikelilingi oleh perbukitan. Bentuk pantainya melekuk ke dalam dan di bagian depannya terdapat pulau Bentenan. Teramati bahwa bentuk pantai ini makin mundur dari tahun ke tahun. Observasi dan pengukuran dilakukan pada bulan November 2008, sebanyak 85 titik telah dipetakan dengan menggunakan GPS dengan koreksi dari peta LPI dan hasilnya dibandingkan dengan beberapa peta terdahulu yaitu Peta Dishidros lembar 334 tahun 1992, Peta Laut No 62 tahun 1985. Perbandingannya menunjukan garis pantai desa Bentenan mengalami perubahan rata-rata sebesar 165 m mundur ke arah daratan dalam selang waktu 1985-2008 (23 tahun). Dalam periode tersebut setiap tahun daerah ini meng-alami kemunduran garis pantai rata-rata 7,17 m.Kata kunci: Bentenan, Garis pantai, Abrasi, Pantai mundur, geomorfologi.